Overriding of the preseptal orbicularis oculi muscle in Caucasian cadavers - Hirohiko Kakizaki (Dove Medical Press, 2009)
Hirohiko Kakizaki1,2, Weng Onn Chan2, Yasuhiro Takahashi3, Dinesh Selva21Department of Ophthalmology, Aichi Medical University, Nagakute, Aichi, Japan; 2South Australian Institute of Ophthalmology and Discipline of Ophthalmology and Visual Sciences, University of Adelaide, Australia; 3Department of Ophthalmology and Visual Sciences, Osaka City University Graduate School of Medicine, Osaka, Japan Abstract: We aimed to microscopically examine whether Caucasian eyelids demonstrate overriding of preseptal orbicularis oculi muscle (OOM) over the pretarsal OOM in both lower and upper eyelids. Full thickness sections of 13 lower eyelids and 11 upper eyelids from seven Caucasian cadavers were examined. In the lower eyelids, all 13 specimens demonstrated clear overriding of preseptal OOM over the pretarsal OOM. The overriding part extended almost to the level of lower eyelid margin. However, in the upper eyelids, only one of the 11 eyelids demonstrated overriding, and the overriding part only extended to the level of mid-tarsal plate. Our result strongly supports the hypothesis of overriding of the preseptal OOM over the pretarsal OOM as an etiology of involutional lower eyelid entropion. The relatively low frequency of upper eyelid overriding preseptal OOM in our study reflects and may explain the rare occurrence of involutional upper eyelid entropion.Keywords: Caucasian, overriding, orbicularis oculi muscle, preseptal, pretarsal